PCB defect detection system using run-length encoding - Zakaria, Muhammad Anif (2017)
The good quality of the printed circuit board is one important thing to produce the highest quality of the electronic devices in the electronics industries. Nowadays, electronic devices were widely used for the development of the technology. In PCB manufacturing many defects have been detected. It was important to produce the zero defect of the PCB to get the best quality of electronic devices. Initially the bare PCBs, which is the PCB without components were inspected by human operators. By using this technique, it was quite costly since the human is tedious, slow, not consistent and highly error due to human error. In order to get the zero defect of the PCB, the automatic inspection has been developed for inspection of PCBs. One of the algorithm that has been built for inspections of PCB is template matching. This technique also cannot solve the previous problem because it is not effective. This method not effective because it was detected the defect only and it cannot classify the defects that have been happen. Besides, these methods need a long time to execute the result. In this project, the technique that quite good than template matching for inspection of PCB was introduced that is run-length encoding (RLE). This technique provides fast, dimensional assessment and quantitative. This technique also saved the time of inspection, save space and more effectively. The main objective using this technique is to reduce the time consuming to inspect the PCB. The secondary objective is to design run-length encoding algorithm able to detect and classify the defect of printed circuit board (PCB). Both of the PCB test and PCB original images was created an analysis window. Each of the analysis windows contents the RLE code. Each of the RLE code of the test image will be compared with the RLE code of the original image. The outcomes by using this technique is it can classify and detect the defect of the PCB. This technique also more effective, save space and not waste the time of inspection.